2013
DOI: 10.1002/ejoc.201300053
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Formal Total Synthesis of Cladosporin

Abstract: A highly diasteroselective and efficient approach for the formal total synthesis of cladosporin is described. Cross‐metathesis, iodocyclization to construct the trans‐2,6‐disubstituted dihydropyran ring system, and an Alder–Rickert reaction to form the aromatic ring were used as the key steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…In 2013, Sridhar et al also reported the total synthesis of cladosporin in a highly diasteroselective and concise manner. Cross-metathesis, iodocyclization to construct the trans-2,6disubstituted dihydropyran ring system, and an Alder-Rickert reaction to form the aromatic ring were used as the key steps [34].The complete synthetic methods for production of cladosporin made it amenable to the generation of a group of scaffolds that can potentially be used to improve drug-like properties.…”
Section: Total Synthesis Of Cladosporinmentioning
confidence: 99%
“…In 2013, Sridhar et al also reported the total synthesis of cladosporin in a highly diasteroselective and concise manner. Cross-metathesis, iodocyclization to construct the trans-2,6disubstituted dihydropyran ring system, and an Alder-Rickert reaction to form the aromatic ring were used as the key steps [34].The complete synthetic methods for production of cladosporin made it amenable to the generation of a group of scaffolds that can potentially be used to improve drug-like properties.…”
Section: Total Synthesis Of Cladosporinmentioning
confidence: 99%
“…Ni 2+ -nitrilotriacetic acid (NTA) agarose was purchased from Qiagen. Cladosporin, 3-epi-isocladosporin, and isocladosporin were synthesized by Debendra K. Mohapatra, CSIR-Indian Institute of Chemical Technology, Hyderabad, India ( 22 , 23 ). Sypro orange dye was obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Heterozygous knockout mutants of Ld LysRS-1 showed reduced growth and were attenuated in their infectivity, indicating the essentiality of this protein. Cladosporin, a fungal secondary metabolite, and 3-epi-isocladosporin, an isoform of isocladosporin ( 22 , 23 ), showed antileishmanial activity in both the promastigote and intracellular amastigote stages in vitro . Both drugs were found to be effective in inhibiting the aminoacylation activity of the recombinant Ld LysRS-1.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, the total synthesis of cladosporin and its diastereomer, isocladosporin, has been reported 20. 21 To better understand PKS assembly and enable analogue production by synthetic biology, we sought to heterologously express and reconstitute cladosporin expression in Saccharomyces cerevisiae . Hence, we sequenced the genome of the producer, Cladosporium cladosporioides UAMH 5063.…”
Section: Methodsmentioning
confidence: 99%